Beats [videorecording (DVD)] - Hurley, Kieran; Welsh, Brian, 1981-; MacDonaldd, Lorn; Ferguson, Brian, 1980-; Fraser, Laura, 1976- (Music Box Films, 2020)
A universal story of friendship, rebellion, and the irresistible power of music as two best friends destined for different futures sneak out to an illegal rave in pursuit of one last crazy night together.